Internal assessment form for private optometry premise industrial training, Bachelor of Optometry (Honours), International Islamic University Malaysia - Md Mustafa, Md Muziman Syah; Yahya, Nurul Ain (2020)
Internal assessment for for industrial training is developed as a tool to evaluate communication skills of optometry students during industrial training at the Ministry of Health facilities, private hospital, private eye clinic, private optometry premise or LASIK center to respective internal assessor or clinical instructor from Department of Optometry and Visual Science, International Islamic University Malaysia.